Strengthening Partnership : ICT Academy APTIKOM - HUAWEI - Tiawan Tiawan; Achmad Benny Mutiara; Rayi Pradono Iswara; Husni Teja; Solikin Solikin; Yunita Anggraini; Ismiyati Ismiyati; Saepul Aripiyanto; Eliza Ariesta; Surjandy Surjandy; Merios Gusan Putra; Radit Suryana; Dani Lukman Hakim; Nilam Atsirina Krisnaputri; Arif Supam Wijaya; Mulya Agung (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
Through strategic cooperation between university and industry, the community service initiative